2015
DOI: 10.1021/ef5019737
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of Self-Aggregation of Asphaltenes at an Oil/Water Interface: Formation and Destruction of the Asphaltene Protective Film

Abstract: It is well known that asphaltene molecules play a significant role in stabilizing emulsions of water in crude oil or diluted bitumen solutions. Molecular dynamics simulations were employed to investigate the aggregation and orientation behaviors of asphaltene molecules in a vacuum and at various water surfaces. Two different continental model asphaltene molecules were employed in this work. It was found that the initially disordered asphaltenes quickly self-assembled into ordered nanoaggregates consisting of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
144
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(155 citation statements)
references
References 64 publications
11
144
0
Order By: Relevance
“…This layer hinders the direct interaction between asphaltenes and water, but serves as a surface for the accumulation of asphaltenes by parallel or T-shape stacking. The asphaltene aggregation will result in a film at the interface (Mikami et al, 2013;Liu et al, 2015). In order to confirm this deduction, we performed an extra simulation with increased concentration of asphaltene (136 g L À1 ) and LHA (100 g L À1 ) by reducing the intersection area of the interface by $42%.…”
Section: Aggregation At the Toluene-water Interfacementioning
confidence: 91%
“…This layer hinders the direct interaction between asphaltenes and water, but serves as a surface for the accumulation of asphaltenes by parallel or T-shape stacking. The asphaltene aggregation will result in a film at the interface (Mikami et al, 2013;Liu et al, 2015). In order to confirm this deduction, we performed an extra simulation with increased concentration of asphaltene (136 g L À1 ) and LHA (100 g L À1 ) by reducing the intersection area of the interface by $42%.…”
Section: Aggregation At the Toluene-water Interfacementioning
confidence: 91%
“…Molecular dynamics simulation studies confirmed that asphaltene aggregation results in the formation of complex structures both in the bulk and at the oil-water interface. [43][44][45][46] The strong selfaggregation of asphaltenes facilitates the adsorption of asphaltenes at oil-water interfaces, which is crucial for the stabilization of oil-water petroleum emulsions, and also the adsorption of asphaltenes onto mineral and metallic surfaces, which leads to plugging and fouling through entire oil production chains. 38 Copyright 2010 American Chemical Society.…”
Section: Asphaltenesmentioning
confidence: 99%
“…Asphaltenes are the heaviest component of the feed oil composed of aliphatic side chains, polyaromatic condensed rings, metallic porphyrins (e.g., Ni and V), and heteroatoms such as sulphur, nitrogen, and oxygen [28]. They confer low API gravity, high viscosity to the feed oil and subsequently their precipitation during upgrading reactions contribute majorly to coke formation.…”
Section: Api Gravity Viscosity and Asphaltenementioning
confidence: 99%